Smart Digital Attack As an Acceleration Drive of Firm Value Creation in Digital Era - Rahmawantari, Dhistianti Mei; Purwoko, Bambang; Suratno, Suratno (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2026)
This study aims to examine and investigate the determinants of firm value creation in this digital era, focused on the role of financial literation as a moderating variable. As the shifting of outside investor perspectives occurred on which key elements can drive accelerated firm value creation in this digital era, business leader should objectively appraise their potential strengths and weaknesses aspect to maximize value creation within their company, so its risk profile will reducing as well. This research resulted a concept called "Smart Digital Attack" in which the position of information technology and financial literacy is central in optimizing firm value in this digital era. The research used quantitative secondary data which is taken from the selected listed retail trading companies annual financial reports at Indonesia Stock Exchange for 2017-2021 period. Descriptive statistic test were also used using Eviews9 software. The research show that only firm leverage have a direct significant effect on its value creation, while other independent variable were not. Moving forward from that, financial literacy successfully managed to moderated the relationship between firm investment decision to its value creation. This research shows the central role of financial literacy as a based for better investment decision, along with optimizing the function of information technology in the company it self to accelerate the value creation.